Perancangan Self Tuning Dua Derajat Kebebasan dengan Metode Fuzzy Logic pada Pengendalian Kecepatan Motor Sinkron Magnet Permanen Menggunakan Metode Vector Control - Charles Ronald Harahap; Endah Komalasari; Nadia Julian Putri (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
Abstract — This paper proposes self tuning Proportional-Integral/Proportional gain controller parameter in a Two Degree of Freedom (2DoF) using fuzzy logic method for speed control of permanent magnet synchronous motor. The self tuning method can automatically determine the PI-P parameters using a fuzzy logic control system. Speed control of the 3-phase permanent magnet synchronous motor is carried out by changing the 3-phase system (a-b-c) to a 2-phase system (direct-quadrature) using the vector control method. SVPWM method is used to modulate six switches on a 3 phase inverter. The results obtained using MATLAB Simulink show that by using a self-tuning fuzzy logic control system, high motor performance results are obtained, where the speed response of the permanent magnet synchronous motor shows that the step response and disturbance response are close to the ideal response. Keywords— Permanent Magnet Synchronous Motor, Self Tuning, Two Degrees of Freedom, Fuzzy Logic, Vector Control.